(untitled) (LEARNing Landscapes, 2010)
This paper illustrates what poetic inquiry may contribute to teaching and learning. By using four samples of my own poetry, I demonstrate how the poetics of self-study can release the inner voice in ways that perhaps more conventional forms of research may not. Poetry removes the insulation between me and my experience to reveal what is "true" for me. Reading my own poetry as text has reinforced my educational convictions: It is who we are, not what we do (Arendt, 1974, p. 179) that will determine the success of our best classroom practices.